A Study of EDI, Processes, Operations and How Employees are Motivated at a Kenyan Bank - Fazal, Waheed Sultanali Muradali (2009)
According to Brabston, L. and Porter, (2004) Information system (IS) and business strategy are essential facets in any organization particularly a bank, we are interested in this sector because it is a major component in Kenya‟s growing economy and so far hardly any research has been done on the efficiency of a Kenyan banks. This dissertation concentrates on a small service enterprise and how IS/IT as well as work motivation strategy can influence the business strategy; we also study how the bank stays in constant communication with the head office.